Pengaruh Pelatihan Proses Keperawatan terhadap Dokumentasi Asuhan Keperawatan di Puskesmas Kabupaten Agam Propinsi Sumatera Barat - Fitra Yeni (Fakultas Keperawatan Universitas Andalas, 2014)
Documentation of nursing care in health centers is very diverse and not according to appropriatestandards thus causing lower quality of care in health centers. The quality of nursing documentation can beimproved by training. This study aimed to determine whether training the family nursing process could improve theability of health center on family care nursing documentation. Quasi- experimental using a one group pre / post testdesign was used as a research method. Documentation of family nursing care was assessed by using nursing carechecklist before and after intervention.The results showed that the family nursing care training could increased theability of nurses to perform family care nursing documentation family (p = 0.000 , p <0.05 ) . The averagedocumentation capability before training was 4.72 and increased to 8.63 after training. This training also showedpositive results for 3 months after the training, the average ability of the documentation is still high, at 8.21. Theresults of the study can be recommended as a good input for educational institutions as well as the HealthDepartment of Health that oversees health centers.